Phases. - Musée d'Ixelles (Ixelles : Musée d'Ixelles, 1964)
Arnould, Marcel ; Baj, Enrico ; Besson, Suzanne ; Brzozowski, Tadeusz ; Buchheister, Carl ; Carlier, Marie ; Cavaliere, Alik ; De Champrel, Henriette ; Corneille ; Daussy, Raymond ; Demeester, Renee ; Devalle, Beppe ; Dova, Gianni ; etc.
Phases, Musée d'Ixelles, du 18.10 au 15.11.1964
boek